Construction of Depth-Structure Shelf-edge Map for Case Study of Kujung Formation, East Java Sea - Rusli, Saifatur; Suparto, Suparto (Makara Journal of Technology, 2004)
Construction of Depth-Structure Shelf-edge Map for Case Study of Kujung Formation, East Java Sea. In general, reflection seismic method has capability to represent sub-surface in time domain. Seismic cross-section that depicts the formation of sub-surface usually use time domain in the format of TWT (Two Way Times). This due to in the process of seismic data acquisition, seismic wave propagates in down-going and up-going manner so that the obtained results from data processing are in the format of TWT seismic vs. shot points. This paper will describe the construction of depth-structure map for case study of Kujung Formation, East Java Sea, as exploration activities of oil companies in Indonesia. Manual data is peaked from seismic cross section and crossed with Vrms data of 3 wells in exploration location. TWT Shelf-edge map of Kujung Formation is divided into 2 parts and the results is crossed with velocitystructure map using Geoframe software CPS-3 so that depth-structure of shelf-edge of Kujung Formation, East Java Sea, is obtained. One of the objectives of this map construction is to get more real visualization of sub surface by using depth domain approach and as sustainable exploration activities of oil companies in Indonesia.